An investigation of monthly mean maximum and absolute maximum temperatures of Bangladesh - AHMED , F. K.; MOBASSHER, A. (MAUSAM, 1991)
Using synoptic and climatological data for 27 years (1951-1977) of 16 stations of Bangladesh, temporal and spatial variations of the ab3olute maximum temperature of Bangladesh have been studied. Empirical probabilities for the interval 35.loC-40.o0C and 40,1° -45.0°C of absolute maximum temperature have been examined. Some correlation characteristics between some pairs of station for some selected months have been analysed. An attempt has been made to explain the cause of temporal and spatial variations of maximum and absolute maximum temperatures from the point of view of synoptic meteorology.